EXPLORING THE RELATIONSHIP BETWEEN MOBILE ADDICTION, INTERPERSONAL RELATIONSHIP AND ACADEMIC BEHAVIOR AMONG YOUNG ADULTS IN TERTIARY INSTITUTIONS (Malaysian Journal of Learning and Instruction, 2022)
Purpose â€“ Smartphones have become part and parcel of life in the 21st century.  However, limited studies have examined the impact of mobile addiction and interpersonal relationship on academic behaviour among adolescents in higher education. Hence, this study was conducted to explore the relationship between these three variables in the Malaysian higher education context. Methodology â€“ A descriptive correlational research design was employed to collect and analyse the data from a total of 150 young adults who responded to an online Google form distributed through a WhatsApp link. The items in the questionnaire were adapted from various doctorate studies. The data were analysed using descriptive and inferential statistics such as mean and standard deviation, correlation and multiple regression. Findings â€“ The study found that adolescents in Higher Education in Malaysia have a moderate level of mobile addiction. The results also established that the three variables, namely mobile addiction, interpersonal relationship, and academic behaviour, were interrelated. The findings suggest that relationship status, interpersonal relationship and gender contributed to the variance in the academic behaviour of adolescents in higher education, with relationship status being the most significant. The study also found that smartphones do not affect the academic behaviour of adolescents. Significance â€“ The findings provide valuable information to help facilitate the monitoring of mobile usage behaviour of adolescents in higher education.